Production of SARS-CoV-2 N Protein-Specific Monoclonal Antibody and Its Application in an ELISA-Based Detection System and Targeting the Interaction Between the Spike C-Terminal Domain and N Protein - Kim, Dongbum; Kim, Jinsoo; Park, Sangkyu; Kim, Minyoung; Baek, Kyeongbin; Kang, Mijeong; Choi, Jun-Kyu; Maharjan, Sony; Akauliya, Madhav; Lee, Younghee; Kwon, Hyung-Joo (Frontiers in Microbiology, 2021)
SARS-CoV-2 infections continue to spread quickly by human‐to‐human transmission around the world. Therefore, developing methods to rapidly detect SARS-CoV-2 with high sensitivity are still urgently needed. We produced a monoclonal antibody that specifically detects the N protein of SARS-CoV-2 and recognizes N protein in cell lysates of SARS-CoV-2-infected Vero cells but not in cell lysates of MERS-CoV- or HCoV-OC43-infected Vero cells. This antibody recognized N protein in SARS-CoV-2 clades S, GR, and GH and recognized N protein in all the SARS-CoV-2 clades to 300 pfu. Previously, we reported that the coronavirus N protein interacts with the C-terminal domain of the spike protein (Spike CD). In this study, we developed an ELISA-based “bait and prey” system to confirm the interaction between SARS-CoV-2 Spike CD and N protein using recombinant fusion proteins. Furthermore, this system can be modified to quantitatively detect SARS-CoV-2 in culture media of infected cells by monitori¬ng the interaction between the recombinant Spike CD fusion protein and the viral N protein, which is captured by the N protein-specific antibody. Therefore, we conclude that our N protein-specific monoclonal antibody and our ELISA-based bait and prey system could be used to diagnose SARS-CoV-2 infections.